Development of the read-out ASIC for muon chambers. Issue 4 (January 2016) - Atkin, E; Bulbakov, I; Gusev, A; Malankin, E; Normanov, D; Sagdiev, I; Shumikhin, V.; Shumkin, O; Ivanov, P; Vinogradov, S; Voronin, A; Samsonov, V.; et al.
Abstract: A front-end prototype ASIC for muon chambers is presented. ASIC was designed and prototyped in the CMOS UMC MMRF 180 nm process via Europractice. The chip includes 8 analog processing channels, each consisting of a preamplifier, two shapers (fast and slow), differential comparator and an area efficient 6 bit SAR ADC with 1.2 mW power consumption at 50 Msps. The chip also includes the threshold DAC and digital serializer. The design has the following features: dynamic range of 100 fC, channel hit rate of 2 MHz, ENC of 1000 e- at 50 pF, power consumption of 10 mW per channel, 6 bit SAR ADC.